Trans-Pacific rebalancing: Thailand case study - Chalongphob Sussangkarn; Deunden Nikomborirak (Asian Development Bank Institute (ADBI), 2011)
Since the Asian financial crisis in 1997, Thailand has become highly dependent on export as the engine of economic recovery and growth. In 2008, the ratio of export to gross domestic product (GDP) was 76.5%. The global economic crisis triggered by the sub-prime loans debacle in the United States has prompted Thailand to rethink her export-led growth strategy. Year-on-year export growth plunged from a positive 22.7% in the third quarter of 2008 to a negative 7.75% in the fourth quarter and remained negative for another four quarters, leading to a negative growth of GDP for five consecutive quarters. This paper examines the options for external and internal economic rebalancing strategies for Thailand. External rebalancing will require Thailand to rely less on the US market for her exports. The paper thus examines the possibility of promoting greater regional trade by means of trade agreements and exchange rate coordination. As for internal rebalancing, the paper emphasizes the need to boost domestic public and private investment in terms of both quantity and quality in order to narrow the current savings' investment gap, bearing in mind the need to ensure fiscal sustainability. Finally, the paper examines broader rebalancing strategies that will help Thailand to become less dependent on exports. These include the need to (1) improve productivity by means of technological acquisition, innovation, and skills development; (2) increase economic efficiency by exposing the non-traded sectors, in particular the service sector, to greater competitive pressures; (3) deepen the production structure and create new dynamic industries; and (4) generate new growth poles.
Keywords: E21; E22; E65; E66; F31; F40; H54; H60; 330; Exportinduziertes Wachstum; Wirtschaftskrise; Außenhandelseffekt; Wirtschaftliche Anpassung; Wirkungsanalyse; Thailand